Atenção aos usuários de drogas no SUS : histórias de encontros e de cuidado - Daniene Cássia dos Santos (2019)
The care given to the people doing harmful use of drugs in Brazil has been through changes since the last years of the 70’s, incorporating conceptions present in the Brazilian Psychiatric Reform, Sanitary Reform and Harm Reduction principles, although they have not been totally detached from former models. These changes range from treatment conception to attention and caring conception; from treatments based in institutionalization, deprivation of rights and different forms of imprisonment to care in territorial based open services. In this qualitative and exploratory research based in the theoretical/methodological references of Ergology combined with Psychosociology we wanted to know the experience of SUS workers in the field of caring for people doing harmful drug use, considering the knowledge, norms and values present in their activity. Narrative interviews were done with workers in this field enabling access to the social history throughout the individual histories. Here are some outstanding points that are fundamental for the work of caring for people doing harmful use of drugs: attention in the training of the worker in his daily routine, by means of reflecting about the situations they experienced, a “supervised learning”, focused on the concept of relationship with the other; worker’s and user’s political education; attention to the material needs of user’s existence and its impact upon the construction of caring; availability to the other; dignified work conditions and different means of hiring workers; dialogue valorization in the management of services, group construction of solutions for the everyday challenges, respect to people. The results pointed out the historical construction of a caring model based on ethical-theoretical-political assumptions: ethical related to the commitment to the user and singularity of care; theoretical based on the caring background including reference of the Psychiatric Reform, Public Health, and Care of people doing harmful use of drugs, among others; political related to the society project in which this Care model is inserted, based in human rights, citizenship and human dignity. They talked about the challenges they confronted, as well as their participation in small or great changes that improved user’s life, contributing to reduce suffering and enabling a less harmful relationship to a certain drug. It was also reported the importance of this work for the people interviewed: the construction of meaning doing this work within their lives.